Implikasi Kebijakan Ekonomi Umar Ibn Khattab terhadap Kebijakan Ekonomi Masa Kini - Sholikul Hadi; Moh Romli (Reslaj : Religion Education Social Laa Roiba Journal, 2021)
In the 1970s and 1980s, scientific studies on Islamic economics and finance in the Middle East and other Muslim countries were initiated, which resulted in the establishment of the Islamic Development Bank and banks and other institutions labeled Islam. In fact, the scope of Islamic economics is much broader than just Islamic finance. The author agrees with Taqyuddin An-Nabhani, that generations of Muslims have been fascinated with Capitalist thinking, because they see its success, without fully understanding the reality of its thoughts, even to the inferior feeling (inferiority) of Islam's ability to produce solutions. The purpose of this research is to examine Umar ibn Khattab's policies in distributing Baitul Maal property and to find out the implications of Umar ibn Khattab's policies on today's economy. This research is a literature research (Library Research) with a historical approach, and collects data from primary materials, namely books concerning Umar ibn Khattab's policies and secondary data, namely relevant supporting books. The stages of this research are the analysis of text or phenomena into its components, grouping the same statements and actions into one component, identifying rules that unite various categories, identifying universal rules that construct statements and inter-relations of actions, and systematics of rules obtained through text procedures. or action. The results of this study, namely that during his caliphate, Umar ibn Khattab had made the necessary regulations and took every possible step to ensure that no one was left to starve, without clothing or a place to live in an Islamic country, including the disabled, helpless. because of illness, old age, widows, unemployment, poor people, people who need assistance regardless of caste, skin color, or beliefs are given financial assistance from Baitul Maal. Umar ibn Khattab's policies can be implied in today's economy, such as the prohibition of selling other people's property without the knowledge of the owner, government intervention in the market, prohibition of hoarding assets, reviving dead land, land ownership limits, on found goods, property that is lawful for the government, and criteria for people who have the right to be prioritized for holding and holding government mandates.